Polycyclic aromatic hydrocarbon (PAH) contamination in the sediments of East Coast Peninsular Malaysia - Md Suhaimi, Elias; Ab. Khalik, Wood; Zaleha, Hashim; Wee, Boon Siong; Mohd Suhaimi, Hamzah; Shamsiah, Ab Rahman; Nazaratul Ashifa, Abdullah Salim; Ariffin, Talib (UKM Publisher, 2007)
The polycyclic aromatic hydrocarbons (PAHs) are pollutants of concern due to their persistent in the marine ecosystem, thus its can cause long-term adverse effect to the marine life. In this study the concentrations of PAHs in east coast Peninsular Malaysia sediments were determined. About ten stations along the east coast of the coastal area were selected to collect sediment samples using grab sampler. The PAHs from the sediment samples were soxhlet extracted using mixture of hexane and dichloromethane (DCM). Fractionation was done using the silica-alumina column. About 17 compounds of the PAHs were determined using the Gas Chromatography-Mass Spectrometer (GCMS model QP5050A). The Σ PAHs was found in range between 0.26μg/g to 0.59μg/g dry weight. The data from the study signified that the main source of PAHs in the sediment of the east coast peninsular Malaysia is originated from the pyrolytic source.